(untitled) - Erika Maskálová; Lucia Mazúchová; Simona Kelčíková; Júlia Samselyová; Lucia Kukučiarová (University of Ostrava, 2021)
Aim: The study aimed to determine childbirth experience and the overall satisfaction of women with childbirth and its related socio-demographic and obstetric factors. Design: A cross-sectional study. Methods: We used the Childbirth Experience Questionnaire (CEQ) on a sample of 161 primiparous women. Results: Total mean CEQ score was 49.78 (SD = 6.02). The best-rated domain was the Perceived safety domain at 2.66 (± 1.90). The worst-rated domain was the Professional support domain at 1.66 (± 1.30). Regarding childbirth satisfaction, the mode of delivery proved to be a related factor, with the highest level of childbirth satisfaction in women after surgical delivery. Conclusion: Providing quality care and creating a positive experience that can contribute to overall birth satisfaction should be a common target of healthcare professionals in caring for parturient women. In order to create a positive childbirth experience, it is necessary to pay increased attention to the management of labor pain relief, to improving the professional support provided by midwives (i.e., through a more sensitive approach to mothers), to promoting the active participation of the mother during childbirth, and to supporting spontaneous vaginal delivery.